Nano color paste for color-changing film
By using nano-color paste for color-changing films with specific ratios, the shortcomings of the existing color-changing films in terms of mechanical and optical properties are solved, and the significant performance improvement of the color-changing films is achieved, which is suitable for color-changing applications of plastic products.
Patent Information
- Application Number
- CN202510038750.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing color-changing films have shortcomings in terms of physical and optical properties, especially in terms of mechanical properties, durability and scintillation characteristics, which are difficult to achieve ideal results.
A nano-color paste for color-changing film is used, which consists of pigment, aqueous polyurethane acrylate emulsion, nano-oxide particles, polyaldehyde resin, alkylphenol polyvinyl ether, ethyl acetate and methyl isobutyl ketone. Through specific ratios and processes, a color-changing film with excellent mechanical properties and optical properties is formed.
The mechanical and optical properties of the color-changing film are significantly improved, and its wear resistance, scratch resistance and adhesion properties in applications are improved, while maintaining good flickering effect.
Smart Images

Figure CN119799076A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation and application of a composite material, and in particular to a nano color paste for a color-changing film. Background Art
[0002] With the rapid development of all walks of life, the market's demand for personalized products for the same products is becoming more and more extensive. Consumers often hope to bring novel and richer changes to the products they use on the basis of pursuing the basic functions of the products. For example, for the automotive market or other product markets that focus on appearance, the use of films of various colors can change the overall or partial appearance of the product by covering and pasting it as a whole. The color-changing film is mainly attached to the surface of the product through polymer materials. The super flexibility brought by the various components of the polymer product can achieve the ideal tortuosity on any curved surface. For the household automobile industry, the color-changing film can fully express the soft texture of the car body surface, and it is easy to remove, does not damage the original car paint, has no residual glue, does not produce any toxic side effects on the paint surface, the human body and nature, and is green and environmentally friendly.
[0003] However, the physical and optical properties of the color-changing film have always been a hot topic in the field of product research and development. How to manufacture a color-changing film product with good mechanical properties, durability, and good flashing properties is worthy of attention. For example, Chinese patent publication CN114752158A provides a method for preparing a color-changing film. Although this type of technology reports that some properties of the color film have been improved, it does not conduct detailed research and reports on the core component pigment composition or color paste of the color film, nor does it further improve the physical and color properties of the color film, and the color-changing film does not obtain good anti-scratch or desorption properties. Summary of the invention
[0004] The present invention aims to solve one or more deficiencies in the above-mentioned prior art.
[0005] According to a first aspect of the present invention, there is provided a nano-color paste for a color-changing film, wherein the nano-color paste comprises the following components in parts by weight:
[0006] 1 to 10 parts by weight of a pigment;
[0007] 10 to 30 parts by weight of an aqueous polyurethane acrylate emulsion;
[0008] 2 to 10 parts by weight of nano oxide particles;
[0009] 3 to 15 parts by weight of polyaldehyde resin;
[0010] 1 to 10 parts by weight of alkylphenol polyvinyl ether;
[0011] 15 to 35 parts by weight of ethyl acetate;
[0012] 1 to 5 parts by weight of methyl isobutyl ketone.
[0013] In a further preferred embodiment, the nano-oxide particles are titanium dioxide nano-oxide particles, and preferably, the average particle size of the titanium dioxide nano-oxide particles is 60 to 80 nanometers; and
[0014] The aqueous polyurethane acrylate emulsion is an aqueous polyurethane acrylate emulsion containing lignin.
[0015] In a further preferred embodiment, the pigment is selected from one or more of iron oxide red, iron oxide yellow, iron oxide black, royal blue, scarlet powder, titanium dioxide, ultramarine blue, phthalocyanine blue and phthalocyanine green.
[0016] In an optional technical solution, the aqueous polyurethane acrylate emulsion containing lignin is prepared by the following method:
[0017] In a reaction container capable of heating and stirring, 500 to 700 grams of dicyclohexylmethane diisocyanate, 80 to 120 grams of polyneopentyl adipate, 90 to 130 grams of polyethylene glycol, 25 to 30 grams of 2,2-bis(hydroxymethyl)propionic acid, 40 to 50 grams of N-ethylpyrrolidone, and 20 to 30 grams of lignin are added; then 0.1 to 0.5 grams of dibutyltin dilaurate is added as a catalytic component, and a pre-reaction is carried out at 60 to 75° C. for 1 to 2 hours; after the pre-reaction is completed, Then add 300 to 500 grams of tert-butyl glycidyl carbonate, 80 to 150 grams of 2-hydroxyethyl acrylate, and 10 to 20 grams of lignin again, and react at 85 to 95° C. for 1 to 2 hours under stirring conditions; then, reduce the temperature of the reaction mixture to below 40° C., then add sodium hydroxide solution for neutralization reaction, and then continue to add 1000 to 1800 grams of deionized water and stir well, then remove the reaction product to obtain a water-based polyurethane acrylate emulsion containing lignin.
[0018] In an optional technical solution, the weight average molecular weight of the added lignin is between 500 and 800; and
[0019] Based on the total mass of the nano-color paste for the color-changing film, the aqueous polyurethane acrylate emulsion containing lignin accounts for 20wt% to 30wt% of the total mass.
[0020] The second aspect of the present invention further provides a color-changing film, wherein the color-changing film contains the nano-color paste for color-changing film as described in the above technical solution.
[0021] In an optional solution, the color-changing film is prepared by the following process steps:
[0022] Add 80 to 150 parts by weight of PVC powder into a container, and then add 20 to 100 parts by weight of diisononyl phthalate as a plasticizer, and stir at a speed of 60 to 200 r / min for 5 to 20 minutes;
[0023] Continue to add 0.05-0.5 parts by weight of antioxidant and 5 to 6 parts by weight of the nano-color paste for color-changing film into the container, and stir at a speed of 100-300 r / min for 5 to 20 minutes;
[0024] The container is evacuated to reduce the air pressure in the preparation container to 0.01 to 0.08 MPa, and the stirring is continued at 50 to 200 r / min for 10 to 30 minutes to obtain the PVC coating material for use;
[0025] A PET protective film with a thickness of 30 to 60 μm is selected, and a layer of PVC coating material with a thickness of 100 to 120 μm is uniformly coated on the protective film as a PVC core layer by slit coating to obtain a laminate;
[0026] The laminate is sequentially passed through a three-stage oven with temperatures of 80°C, 90°C, and 60°C for drying and curing, and then rolled up for later use;
[0027] Laminating a layer of calendered PVC bottom film on one side of the PVC core layer by heating and laminating;
[0028] The acrylic pressure-sensitive adhesive layer is coated on one side of the PVC base film by slit extrusion coating for bonding, the dry adhesive thickness is controlled at (30-60 μm) ± 0.5 μm, and the color-changing film is rolled up.
[0029] The nano-color paste and color-changing film products obtained according to this embodiment are particularly suitable for combining with PVC base film to form a color-changing film. They have good bonding and physical parameter characteristics for plastic products, and significantly improve the mechanical properties and optical properties of the film surface. This will be described in more detail below.
[0030] In the following, the technical solutions and advantages of the present invention will be explained and described in more detail in conjunction with specific implementation methods. It should be understood that the contents presented in the specification and specific implementation methods are only for the purpose of more clearly illustrating the technical solutions and advantages of the present invention, and do not limit the protection scope of the present invention. Those skilled in the art can obtain the changed technical solutions based on the disclosure of the specification for various reasonable transformations. As long as they do not deviate from the spirit of the present invention, the various changed technical solutions should be understood to be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide a further understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the specific embodiments of the present application, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.
[0032] Figure 1 It is a schematic diagram of the cross-section layers of the nano-color paste color-changing film produced according to the embodiments and manufacturing examples of the present invention. DETAILED DESCRIPTION
[0033] The present invention is described in more detail hereinafter to facilitate understanding of the invention.
[0034] Before describing the specific implementation scheme, it should be noted that those skilled in the art can select appropriate raw materials according to the enlightenment and teaching of the present disclosure, and use relevant testing equipment to perform relevant tests and obtain corresponding results. For raw materials without specific manufacturers or pathways, those skilled in the art can select raw materials that meet corresponding requirements as reaction starting materials according to the disclosure and requirements of this specification. The reaction raw materials of the process part compounds are derived from the initial products synthesized in the preamble step of the present invention, which can also be understood according to the present disclosure.
[0035] First, the main raw materials used in the present invention and the corresponding acquisition channels or raw material origins are listed in Table 1. It should be noted that the raw materials not described in the present invention are raw material varieties that can be obtained by those skilled in the art based on common technical knowledge and existing market products.
[0036] Table 1: Sources of some raw materials used in the present invention
[0037]
[0038]
[0039] The inventor first describes some test conditions and methods for the color-changing film containing the color paste component of the present invention. In fact, in this field, ordinary technicians know how to test and characterize the characteristics and data of each color-changing film.
[0040] 1. Flashing effect
[0041] The sparkle effect of the color-changing film is one of the parameters that characterizes whether the color-changing film is smooth, bright, and has a good appearance. A good sparkle effect has a good market-aiding effect in certain applications of color-changing films, especially in the color change of automobile surfaces. Regarding a measurement system of such a measuring device, the Byk-mac system provided by the German company Byk-Gardner GmbH can be used. It can measure the degree of sparkle for sheet materials. Under the characterization system of this system, the sparkle level is a function of the following two parameters: the sparkle area, which corresponds to the number of light reflections in a specified measurement; and, the sparkle intensity, which corresponds to the intensity of the light reflection. The sparkle level is usually expressed as a number between 0 (basically no sparkle) and 10 (highest sparkle).
[0042] 2. Pencil hardness test
[0043] For the film surface containing color paste that is exposed to the external environment in actual use, pencils of different hardness are used as scratching tools (typical pencil hardness can include 6B, 5B, 4B, 3B, 2B, B, HB, H, 2H, 3H, 4H, 5H and other levels). On the simulated assembled color-changing film sample without surface release film or protective film, 1200 grams of force is applied in a 45° direction with a stroke of 15 mm. Three scratches are made at different positions to observe whether there are obvious scratches on the appearance of the sample. The hardest pencil number that cannot scratch the paint film is the hardness of the paint film.
[0044] 3. Adhesion test
[0045] Test method: For the film surface containing color paste that is exposed to the external environment in actual use, use the back of a scalpel to scratch 8-9 scratches on the coating, at least two of which are at a 90° angle to the other scratches, to form a grid on the surface with a side length of 2-3 mm. Make sure that each scratch cuts into the base material (bottom layer PVC). Brush 5 times in both directions of the scratch. Put 3M tape (3M TM VHB TM Stick the tape on the surface, press the tape with your fingertips to ensure close contact with the test layer, and after 5 minutes, peel off the tape regularly from the free end of the tape at an angle of 60° within 1-1.5 seconds;
[0046] Level classification:
[0047] Level 0: The edges of the cut are completely smooth, and the squares of the grid have not peeled off;
[0048] Level 1: The area of the peeled portion is no more than 5% of the area of the tape in contact with the surface;
[0049] Level 2: The area of the peeled portion is greater than 5% of the area of the tape in contact with the surface, but not more than 15%;
[0050] Level 3: The area of the peeled portion is greater than 15% of the area of the tape in contact with the surface, but not more than 35%;
[0051] Grade 4: The area of the peeled portion is greater than 35% and not more than 65% of the area of the tape in contact with the surface.
[0052] 4. Wear resistance test
[0053] Similar to the above test objects, the JM-V abrasion tester provided by Shenzhen Xiangmin Instrument Co., Ltd. was used to grind the surface of the installed color-changing film under the action of 200 grams of force, and the number of times (number of turns) the rubber wheel rotated when the coating was exposed to the base material was recorded.
[0054] The test methods and processes used in the embodiments of the present invention and the comparative experiments will be described together with the description of the embodiments as necessary. Those skilled in the art can understand and implement the corresponding processes and tests based on the contents disclosed in the specification.
[0055] In an embodiment of the present invention, a composition or a process step may include the components / steps described above and may also have other components or steps. However, it may be preferred that the composition or method described in the embodiment of the present invention is composed only of the steps described above and does not include other components (except for unavoidable impurities or conventional processing steps). For example, the nano-color paste composition of the embodiment of the present invention may include the components described above and may also have other auxiliary components; however, preferably, the nano-color paste composition of the present invention is composed only of the components described above and does not significantly include other components or chemicals.
[0056] Preparation Example 1
[0057] As one of the elements of this embodiment, a process for preparing an aqueous polyurethane acrylate emulsion containing lignin is first described herein.
[0058] This preparation example describes a typical method for preparing a waterborne polyurethane acrylate emulsion containing lignin. In a reaction kettle equipped with a stirring blade and a peripheral cooling water pipe, 600 g of dicyclohexylmethane diisocyanate (H 12MDI), 100 g of polyneopentyl adipate, 100 g of polyethylene glycol, 25 g of 2,2-bis(hydroxymethyl)propionic acid, 45 g of N-ethylpyrrolidone, and 25 g of lignin; then 0.2 g of dibutyltin dilaurate is added as a catalytic component, and the reaction is carried out at 70° C. for 1 hour; after the pre-reaction stage is completed, 400 g of tert-butyl glycidyl carbonate, 100 g of 2-hydroxyethyl acrylate, and 15 g of lignin are added, and the reaction is carried out at 90° C. for 1 hour (at this time, the content of residual isocyanate is detected to be less than 0.05 wt %), the temperature of the reaction mixture is reduced to below 40° C., and then 10 g of 15 wt % sodium hydroxide solution is added for neutralization reaction, and then 1300-1500 g of water is continuously added for sufficient stirring, and then the reaction product is removed to obtain an aqueous polyurethane acrylate emulsion containing lignin (the product solid content is about 37 wt %).
[0059] In the actual preparation process, according to different scenarios of industrial production and laboratory testing, the usage of each component can be proportionally expanded or reduced, or appropriately adjusted within the scope of use.
[0060] Example
[0061] This embodiment introduces a (nano) color paste composition suitable for use in color-changing films. In the embodiment, the composition typically comprises the following components (calculated in parts by weight):
[0062] Embodiment 1:
[0063] 5 parts by weight of phthalocyanine green pigment (BASF Green L8730), 15 parts by weight of aqueous polyurethane acrylate emulsion containing lignin described in the preparation example, 4 parts by weight of nano titanium dioxide, 8 parts by weight of polyaldehyde resin, 5 parts by weight of alkylphenol polyvinyl ether, 33 parts by weight of ethyl acetate, and 5 parts by weight of methyl isobutyl ketone (MIBK) as components of the nano color paste composition. The average particle size of the nano titanium dioxide is 60-80 nanometers.
[0064] In a typical preparation process, the preparation process of the color paste composition includes the following steps:
[0065] Step 1) The determined components of the aqueous polyurethane acrylate emulsion containing lignin, polyaldehyde resin, alkylphenol polyvinyl ether, ethyl acetate and methyl isobutyl ketone are kept at a temperature of 45° C. to 55° C. and are fully stirred and mixed;
[0066] Step 2) adding phthalocyanine green pigment and nano titanium dioxide, and preliminarily mixing at a stirring speed of 100-200 rpm;
[0067] Step 3) The preliminarily mixed materials are sent to a centrifugal sand grinder, and 0.5-0.6 mm zirconium dioxide is used as a medium grinding ball to fully grind and mix the above mixture for 2-5 hours to finally obtain a nano-color paste composition used for the color-changing film.
[0068] In the following examples, the same preparation process as in Example 1 was used, and only the composition ratio of the raw materials was partially adjusted. As shown in Table 2.
[0069] Table 2: Raw material ratios of nano-color paste compositions of some examples
[0070]
[0071]
[0072] Comparative Example 1
[0073] In Comparative Example 1, the same raw material types and color paste preparation process as in Example 1 were used, but the difference was that the ratio of each raw material was changed, and the content ratio of the aqueous polyurethane acrylate emulsion containing lignin was significantly reduced (accounting for less than 10%wt of the total composition). Specifically,
[0074] 5 parts by weight of phthalocyanine green pigment (BASF Green L8730), 5 parts by weight of aqueous polyurethane acrylate emulsion containing lignin described in the preparation example, 2 parts by weight of nano titanium dioxide, 10 parts by weight of polyaldehyde resin, 5 parts by weight of alkylphenol polyvinyl ether, 35 parts by weight of ethyl acetate, and 5 parts by weight of methyl isobutyl ketone (MIBK) as components of the nano color paste composition. The average particle size of the nano titanium dioxide is 60-80 nanometers.
[0075] Comparative Example 2
[0076] Similarly, in Comparative Example 2, the same raw material types and color paste preparation process as in Example 1 were used, but the difference was that the ratio of each raw material was changed, and the content ratio of the aqueous polyurethane acrylate emulsion containing lignin was significantly increased (accounting for more than 30%wt of the total composition). Specifically,
[0077] 5 parts by weight of phthalocyanine green pigment (BASF Green L8730), 35 parts by weight of aqueous polyurethane acrylate emulsion containing lignin described in the preparation example, 2 parts by weight of nano titanium dioxide, 10 parts by weight of polyaldehyde resin, 5 parts by weight of alkylphenol polyvinyl ether, 35 parts by weight of ethyl acetate, and 5 parts by weight of methyl isobutyl ketone (MIBK) as components of the nano color paste composition. The average particle size of the nano titanium dioxide is 60-80 nanometers.
[0078] Comparative Example 3
[0079] Comparative Example 3 uses a component ratio and process similar to that of Example 1. The difference is that in the component ratio of the color paste emulsion used in Comparative Example 3, the aqueous polyurethane acrylate emulsion containing lignin is not used, but cellulose acetate butyrate in the same weight portion is used instead.
[0080] Comparative Example 4
[0081] Comparative Example 4 uses the same component ratio and process as Example 1. The difference is that in the aqueous polyurethane acrylate emulsion containing lignin used in Comparative Example 4, a component with a larger average molecular weight of 1500 is used in the lignin component.
[0082] Comparative Example 5
[0083] Comparative Example 5 uses the same component ratio and process as Example 1. The difference is that the nano titanium dioxide material used in Comparative Example 5 has an average particle size of 25 nanometers.
[0084] Application Manufacturing Example
[0085] After the examples and comparative examples, the inventors further elaborate and describe in more detail the manufacturing process of the color-changing film using the nano-color paste in the embodiment / comparative scheme of the present invention, and the test structure mentioned in this specification is based on the nano-color paste color-changing film manufactured in this exemplary manufacturing example. However, it should be noted that the concept of the present invention is not limited to only one manufacturing process of the color-changing film.
[0086] In typical color-changing film structures and products (see Figure 1 ), including a PVC core layer 100 with a color-changing color paste, a temporary protective layer 101 (a release film that can be removed after application to increase the color effect of the core layer) is directly disposed on the upper surface of the PVC core layer 100; a PVC bottom layer 102 (which can be a common calendered PVC layer) can be disposed under the PVC core layer 100, and an adhesive layer 103 (which can be a pressure-sensitive adhesive) can also be disposed under the PVC bottom layer 102. If the color-changing film needs to be stored for a long time without use, an adhesive protective layer (not shown) can also be selectively disposed under the adhesive layer 103. A typical preparation process containing the nano-modified color paste of the present invention is as follows.
[0087] Add 100 parts of PVC powder into a container, and then add 30 to 80 parts of diisononyl phthalate (DINP) plasticizer, and stir at a speed of 100 r / min for 10 minutes.
[0088] Continue to add 0.1 parts by weight of antioxidant (Songnox 1010) and 5 to 6 parts of the color paste composition prepared in the example or comparative example into the container, and stir at a speed of 200 r / min for 10 minutes.
[0089] The preparation environment was evacuated to reduce the air pressure in the preparation container to 0.05 MPa, and the equipment was slightly heated to a temperature of 35 to 40° C. The stirring was continued at 100 r / min for 20 minutes to obtain the PVC coating for use.
[0090] A 50 μm thick PET protective film is selected (as a temporary protective layer 101, which can be removed when the actual product is used or tested), and a layer of 100-120 μm thick PVC coating (i.e., PVC core layer 100, which has the above-mentioned PVC material containing the color paste component of the experimental scheme) is evenly coated on the protective film by slit coating.
[0091] The laminate was sequentially passed through a three-stage oven with temperatures of 80°C / 90°C / 60°C for drying and curing, and then rolled up for use.
[0092] A layer of calendered PVC bottom film (as the PVC bottom layer 102 ) is laminated on one side of the PVC core layer 100 by means of heat lamination.
[0093] An acrylic pressure-sensitive adhesive layer is coated on one side of the PVC base film of the prepared film by slit extrusion coating for lamination (as adhesive layer 103), the dry adhesive thickness is controlled at 50±0.5 μm, and the finished film is rolled up.
[0094] If long-term storage is required, a release protective film (not shown in the figure) can be selectively set again under the adhesive layer 103. If it is used in a short period of time, this process can be omitted and the prepared finished film can be directly rolled up for transportation, storage or use.
[0095] Test Case
[0096] By applying the solutions of each preparation example, embodiment, and comparative example to the manufacturing example described above, the test results of the color-changing film described in this embodiment can be obtained. For the corresponding test results, please refer to the content shown in the following Table 3:
[0097] Table 3: Color-changing film properties obtained from the color paste products of the examples and comparative experiments
[0098] Flicker Level Hardness test Adhesion Wear test (circle) Example 1 8 3H Level 0 755 Example 2 7 3H Level 0 742 Example 3 7 3H Level 0 760 Example 4 7 2H Level 1 715 Comparative Example 1 6 B Level 2 688 Comparative Example 2 5 2H Level 0 720 Comparative Example 3 5 2B Level 3 575 Comparative Example 4 5 B Level 2 690 Comparative Example 5 4 2H Level 0 704
[0099] In the embodiments that all have good color-changing film glittering performance, the inventors found that when the mass content of the aqueous polyurethane acrylate emulsion containing lignin in the color film component is close to 20wt%, the glittering effect is better, and when the mass of the aqueous polyurethane acrylate emulsion is significantly greater than 30%wt, a certain degree of decline occurs; the inventors believe that they are not subject to any theory, but infer that this may be related to the high adhesion of the aqueous polyurethane acrylate emulsion containing lignin. Therefore, in an embodiment of the present invention, it is preferred that the mass of the aqueous polyurethane acrylate emulsion containing lignin in the color film component accounts for 20wt% to 30wt% of the total mass of the total color film component; in addition, when the average particle size of titanium dioxide is too small (less than 50nm), the glittering effect decreases, which is not preferred for certain applications of color-changing films, such as the modification of private cars, because the market and customers usually need to improve the surface of the original car paint that is not bright enough, so the reflection effect of high metallic luster is more preferred. In terms of hardness testing, the color film containing a specific lignin component using the specific color paste component of the present invention shows excellent scratch resistance. When the formula of the present invention is not used, or the size and content of the lignin used are not good, the scratch resistance performance is reduced. Similarly, the modified color paste of the aqueous polyurethane acrylate emulsion containing lignin according to the embodiment of the present invention has good adhesion and wear resistance. In an embodiment of the present invention, for example, the molecular weight of lignin is greater than 500, but preferably between 500-800, and the average particle size of nano titanium dioxide is preferably between 50-100 nanometers. The nano color paste of this embodiment is particularly suitable for combining with a PVC base film to form a color-changing film, and it has good bonding and physical parameter characteristics for plastic products.
[0100] According to the implementation scheme and technical contents recorded in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various formal and detailed replacements or changes can be made to these embodiments without departing from the gist and scope of the invention of the present claims and their equivalent technical solutions. The embodiments described herein should be considered to be illustrative only and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered to be applicable to similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the technical solutions of the claims, and all changes within the scope of the claims and their equivalents are interpreted as being included in the technical solutions of the present disclosure.
Claims
1. A nano color paste for color-changing film, characterized in that: The nano color paste comprises the following components in parts by weight: 1 to 10 parts by weight of a pigment; 10 to 30 parts by weight of an aqueous polyurethane acrylate emulsion; 2 to 10 parts by weight of nano oxide particles; 3 to 15 parts by weight of polyaldehyde resin; 1 to 10 parts by weight of alkylphenol polyvinyl ether; 15 to 35 parts by weight of ethyl acetate; 1 to 5 parts by weight of methyl isobutyl ketone.
2. The nano color paste for color-changing film according to claim 1, characterized in that: The nano-oxide particles are titanium dioxide nano-oxide particles, and preferably, the average particle size of the titanium dioxide nano-oxide particles is 60 to 80 nanometers; and The aqueous polyurethane acrylate emulsion is an aqueous polyurethane acrylate emulsion containing lignin.
3. The nano color paste for color-changing film according to claim 1 or 2, characterized in that: The pigment is selected from one or more of iron oxide red, iron oxide yellow, iron oxide black, royal blue, scarlet powder, titanium dioxide, ultramarine blue, phthalocyanine blue and phthalocyanine green.
4. The nano-color paste for color-changing film according to any one of claims 1 to 3, characterized in that: The aqueous polyurethane acrylate emulsion containing lignin is prepared by the following method: In a reaction container capable of heating and stirring, 500 to 700 grams of dicyclohexylmethane diisocyanate, 80 to 120 grams of polyneopentyl adipate, 90 to 130 grams of polyethylene glycol, 25 to 30 grams of 2,2-bis(hydroxymethyl)propionic acid, 40 to 50 grams of N-ethylpyrrolidone, and 20 to 30 grams of lignin are added; then 0.1 to 0.5 grams of dibutyltin dilaurate is added as a catalytic component, and a pre-reaction is carried out at 60 to 75° C. for 1 to 2 hours; after the pre-reaction is completed, Then add 300 to 500 grams of tert-butyl glycidyl carbonate, 80 to 150 grams of 2-hydroxyethyl acrylate, and 10 to 20 grams of lignin again, and react at 85 to 95° C. for 1 to 2 hours under stirring conditions; then, reduce the temperature of the reaction mixture to below 40° C., then add sodium hydroxide solution for neutralization reaction, and then continue to add 1000 to 1800 grams of deionized water and stir well, then remove the reaction product to obtain a water-based polyurethane acrylate emulsion containing lignin.
5. The nano color paste for color-changing film according to claim 4, characterized in that: The weight average molecular weight of the added lignin is between 500 and 800; and Based on the total mass of the nano-color paste for the color-changing film, the aqueous polyurethane acrylate emulsion containing lignin accounts for 20wt% to 30wt% of the total mass.
6. A color-changing film, characterized in that: The color-changing film contains the nano-color paste for color-changing film according to any one of claims 1 to 5.
7. The color-changing film according to claim 6, characterized in that: The color-changing film is prepared by the following process steps: Add 80 to 150 parts by weight of PVC powder into a container, and then add 20 to 100 parts by weight of diisononyl phthalate as a plasticizer, and stir at a speed of 60 to 200 r / min for 5 to 20 minutes; Continue to add 0.05-0.5 parts by weight of antioxidant and 5 to 6 parts by weight of the nano-color paste for color-changing film into the container, and stir at a speed of 100-300 r / min for 5 to 20 minutes; The container is evacuated to reduce the air pressure in the preparation container to 0.01 to 0.08 MPa, and the stirring is continued at 50 to 200 r / min for 10 to 30 minutes to obtain the PVC coating material for use; A PET protective film with a thickness of 30 to 60 μm is selected, and a layer of PVC coating material with a thickness of 100 to 120 μm is uniformly coated on the protective film as a PVC core layer by slit coating to obtain a laminate; The laminate is sequentially passed through a three-stage oven with temperatures of 80°C, 90°C, and 60°C for drying and curing, and then rolled up for later use; Laminating a layer of calendered PVC bottom film on one side of the PVC core layer by heating and laminating; The acrylic pressure-sensitive adhesive layer is coated on one side of the PVC base film by slit extrusion coating for bonding, the dry adhesive thickness is controlled at (30-60 μm) ± 0.5 μm, and the color-changing film is rolled up.
Citation Information
Patent Citations
Polyurethane emulsion, preparation method of the polyurethane emulsion, nanometer color paste, preparation method of the nanometer color paste, ultraviolet light-cured coating composition and preparation method of the ultraviolet light-cured coating composition
CN102618020A
Casting-grade PVC color-changing film and preparation method thereof
CN116496709A
High-transmittance blue paste for automobile color-changing film and preparation method of high-transmittance blue paste
CN119144202A